Effectiveness of Eight Weeks Aerobic and Aerobic-resistance Cardiac Rehabilitation Exercise Training on Hemorheologic Variables among Middle-aged Men with Coronary Artery Disease - Razzaghi, Abolghasem; Sadeghi, Heydar; Johari Moghadam, Adel; Azma, Kamran; Raeissadat, Seyed Ahmad (Journal of Clinical Physiotherapy Research, 2021)
Introduction: Hemorheologic disorders are the most important causes of impaired circulation and cardiovascular events. It is also documented that regular and continuous exercise training could improve vascular adaptation to exercise and provide protection against major cardiovascular events. The aim of this study was to evaluate effectiveness of eight-week cardiac rehabilitation exercise by aerobic and aerobic-resistance methods on hemorheologic variables among middle-aged men with coronary artery disease (CAD). Materials and Methods: The present quasi-experimental study was carried out on 51 middle-aged men with CAD aged 45-65 years. Participants were randomly divided into three groups including aerobic exercise, aerobic-resistance exercise, and control group. The experimental groups performed sub-maximal aerobic exercises for eight weeks. Exercise protocol consisted rehabilitation exercises for three sessions a week. In addition to aerobic exercise, aerobic-resistance group received two sessions of resistance exercise using free weights per week for 15 minutes. Results: There was a significant improvement in all hemorheologic variables including fibrinogen concentration (P=0.001), hematocrit concentration (P=0.002), and erythrocyte sedimentation rate (P=0.001) in both aerobic and aerobic-resistance exercise groups compared to the control group. There was also a significant decrease of mentioned hemorheologic variables in aerobic-resistance group compared to aerobic group. Conclusion: Our study showed that eight-week cardiac rehabilitation exercises, especially aerobic-resistance exercise training, could improve the blood hematologic variables in middle-aged men with CAD.